A message complexity oriented design of distributed algorithm for long-lived multicasting in wireless sensor networks. (30th November 2009) - Guo, Song; Guo, Minyi; Leung, Victor C.M.
We consider an optimisation problem in Wireless Sensor Networks (WSNs) that is to find a multicast tree rooted at the source node and including all the destination nodes such that the lifetime of the tree is maximised. While a recently proposed distributed algorithm for this problem guarantees to obtain optimal solutions, we show that its high message complexity may prevent such contribution from being practically used in resource-constrained WSNs. In this paper, we proposed a new distributed sub-optimal algorithm that achieves a good balance on the algorithm-optimality and message complexity. In particular, we prove that it has a linear-message complexity. The trade-off between algorithm sub-optimality and message complexity is also studied by simulations.